FGFR inhibitors combined with nab-paclitaxel - A promising strategy to treat non-small cell lung cancer and overcome resistance - Ma, Feng; Zhu, Xinhai; Niu, Yuchun; Nai, Aitao; Bashir, Shoaib; Xiong, Yan; Dong, Yunlong; Li, Yin; Song, Jian; Xu, Meng (Frontiers in Oncology, 2023)
Lung cancer has high morbidity and mortality rates worldwide, and NSCLC accounts for 85% of all lung cancer cases. Despite the development of targeted therapies and immunotherapy, many NSCLC patients do not effectively respond to treatment, and new treatment strategies are urgently needed. Aberrant activation of the FGFR signaling pathway is closely related to the initiation and progression of tumors. AZD4547, which is a selective inhibitor of FGFR 1-3, can suppress the growth of tumor cells with deregulated FGFR expression in vivo and in vitro. However, further exploration is needed to determine whether AZD4547 can play an antiproliferative role in tumor cells without deregulated FGFR expression. We investigated the antiproliferative effect of AZD4547 on NSCLC cells without deregulated FGFR expression. In vivo and in vitro experiments showed that AZD4547 exerted a weak antiproliferative effect on NSCLC cells without deregulated FGFR expression, but it significantly enhanced the sensitivity of NSCLC cells to nab-paclitaxel. We found that AZD4547 combined with nab-paclitaxel suppressed the phosphorylation of the MAPK signaling pathway, led to cell cycle arrest in the G2/M phase, promoted apoptosis, and inhibited cell proliferation more substantially than nab-paclitaxel alone. These findings provide insight into the rational use of FGFR inhibitors and personalized treatment of NSCLC patients.